Development of bio-based advanced composites with transport structures in mind - Nyström, Birgitha; Joffe, Roberts; Rozite, Liva (Luleå tekniska universitet, Materialvetenskap, 2011)
A world wide eco race is taking place in the transportation sectors. This race is driven by factors such as climate change awareness and oil prices. The main goal is reduction of fossil raw material dependency and minimizing the overall carbon foot-print. As well as the entering on the market of new types of hybrid engines with low fuel consumption and electric cars there is an increasing push from many car producers to incorporate renewable, recyclable lightweight materials in their vehicles. Swerea SICOMP and Luleå University of Technology have been involved in R&D on bio-based materials for transportation applications for more than 10 years. The results from ongoing research projects with focus on bio-based structural applications for transportation applications are promising. Fibres that are being studied include manmade regenerated cellulose, cellulose nano fibrils and whiskers as well as high quality flax fibre fabrics. Several new bio-based or partly bio-based resins that are entering the market are being evaluated. Results regarding processability, mechanical performance, durability and design & manufacturing show that the latest development in the field of bio-based constituents (reinforcing fibres, core materials and resins) for composites are taking large steps forward and new green options for the transportation sector will soon be available. Godkänd; 2011; 20111005 (joffe)